Modeling secular and age differences between highly trained junior basketball players on anthropometric and fitness tests - Drinkwater, E.; Pyne, D.; Hopkins, W.; Hunt, P. (Journal of Science and Medicine in Sport, 2003)
Aim: To quantify concerns of Basketball Australia coaches regarding declining fitness and body size in junior basketball players entering State and National programs and quantify variation between players. Methods: Effects of age (15-19 y) and year (1996-2001) at recruitment on anthropometric (height, mass, skinfolds) and court tests (20 m sprint, vertical jump, shuttle run) conducted by Basketball Australia were analysed by mixed modelling. Subjects were 896 females (811 State players, 85 National players) and 968 males (854 State players, 114 National players) age 15.9 ± 1.1 y (mean ± SD) tested 2.5 ± 1.9 times. Results: The secular trend of scores comparing differences between 1996 and 2001 for all four groups (State Male, State Female, National Male, National Female) demonstrated a pattern of declining fitness in shuttle run (range: -1.9 to 0.5%), 20 m sprint time (-1.8% to 8.1), vertical jump (-3.8 to 12%), height (-2.0 to 2.5%), mass (-7.4 to 5.3%), and skinfolds (-18 to 18%) in newly recruited players. Differences between 15- and 19-year old players of different groups were small to moderate in shuttle run (2.5 to 11%), 20 m sprint (-0.8 to 2%), vertical jump (-1.6 to 7.4%), height (-4.6 to 5.3%), and mass (0.9 to 11%) while skinfold differences varied widely between groups (-34 to 23%). While variation of tests tended to vary widely (4.1 - 32.5%) the range of variation between groups in a test tended to be quite small (<6%). Conclusion: (a) there was a secular decline of sprint, vertical jump, height, and skinfolds that indicates programs were recruiting less fit players in 2001 than 1996; and (b) coaches should look to recruiting older players as one option for increasing the fitness levels of teams.